Modeling a Solar-Powered IoT Smart Home - Raji, A.; Adunola, F. O.; Airoboman, A. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 1970)
The concept of smart homes has gained more interest in recent years, as the unwavering advancement in IoT technologies enable devices to operate and communicate autonomously. As urbanization accelerate and energy demand increase, on-grid energy system faces significant challenges, including high carbon emissions, energy inefficiency, and reliance on nonrenewable energy sources. The incorporation of solar power into this system not only reduces dependence on traditional energy sources but also promotes sustainability by utilizing clean, renewable energy. The research Present a comprehensive model that addresses these challenges, focusing on energy efficiency, seamless IoT integration, user interaction, scalability. A potable model called SMHome system is powered by solar energy, developed with an algorithm for monitoring and controlling the home autonomously over the internet. The Arduino Nano collects data from various sensors (temperature, motion) and communicates with the ESP8266 for Wi-Fi connectivity. The ESP8266 sends this sensor data to a cloud platform via TCP, allowing remote monitoring and control through a mobile app. Integration with the IFTTT app enables automation, where specific triggers from the sensors can initiate actions, such as sending notifications or controlling devices based on user-defined conditions. The proposed SMHome system is structured in a form that a potable box powered by solar energy can only be easily and efficiently control appliances over the Internet and support home safety with autonomous operation. By integrating solar energy with IoT technologies, the research demonstrates the potential for improved energy management, reduced environmental impact and enhanced quality of life for residents.